Lactate from the tumor microenvironment - A key obstacle in NK cell-based immunotherapies - Jedlička, Marek; Feglarová, Tereza; Janstová, Lucie; Hortová-Kohoutková, Marcela; Frič, Jan (Frontiers in Immunology, 2022)
Recent findings about the new roles of lactate have changed our understanding of this end product of glycolysis or fermentation that was once considered only a waste product. It is now well accepted that lactate acts as a signaling molecule and fuel source for cancer cells in a glucose-restricted environment. Moreover, lactate and lactate dehydrogenase are markers of poor prognosis of many cancers and regulate many functions of immune cells. The presence of lactate in the tumor microenvironment (TME) leads to polarization of the immunosuppressive phenotypes of dendritic cells and impairs the cytotoxic abilities of T cells and NK cells, and as such lactate is a major obstacle to immune-cell effector functions and the efficacy of cell-based immunotherapies. Emerging evidence suggests that lactate in the TME might be a novel therapeutic target to enhance the immunotherapeutic potential of cell-based therapies. This review describes our current understanding of the role of lactate in tumor biology, including its detrimental effects on cell-based immunotherapy in cancer. We also highlight how the role of lactate in the TME must be considered when producing cell therapies designed for adoptive transfer and describe how targeted modulation of lactate in the TME might boost immune-cell functions and positively impact cellular immunotherapy, with a focus on NK cell.